Observations of circumstellar disks in scattered light with SPHERE at the VLT - Boccaletti, Anthony (Comptes Rendus. Physique)
The technological developments initiated in the early 21$^{\rm st}$ century have led to the implementation of “planet finders” instruments on 8-m class telescopes which are in operation since 2014-2015. Such facilities are at the inception of significant progresses in the study of exoplanetary systems by enabling high contrast imaging of the environment of young nearby stars. One of the most productive science in this field is certainly the observations at high angular resolution of circumstellar disks, from the very young gas-rich protoplanetary disks all the way to more elusive dust-rich debris disks. In this paper, we summarize the main results obtained for these two categories of objects focusing on their morphological characteristics, as well as on the measurement of optical properties of the small dust particles to which the near IR spectral range is sensitive to. We mostly provide exemples based on observations performed with the SPHERE instrument at the VLT.